Sepsis Disrupts Mitochondrial Function and Diaphragm Morphology - Oliveira, Thamires Siqueira; Santos, Anderson Teixeira; Andrade, Cherley Borba Vieira; Silva, Johnatas Dutra; Blanco, Natália; Rocha, Nazareth de Novaes; Woyames, Juliana; Silva, Pedro Leme; Rocco, Patricia Rieken Macedo; da-Silva, Wagner Seixas; Ortiga-Carvalho, Tânia Maria; Bloise, Flavia Fonseca (Frontiers in Physiology, 2021)
Background The diaphragm is the primary muscle of inspiration, and its dysfunction is frequent during sepsis. However, the mechanisms associated with sepsis and diaphragm dysfunction are not well understood. In this study, we evaluated the morphophysiological changes of the mitochondrial diaphragm 5 days after sepsis induction. Methods Male C57Bl/6 mice were divided into two groups, namely, cecal ligation and puncture (CLP, n = 26) and sham-operated (n = 19). Mice received antibiotic treatment 8 h after surgery and then every 24 h until 5 days after surgery when mice were euthanized and the diaphragms were collected. Also, diaphragm function was evaluated in vivo by ultrasound 120 h after CLP. The tissue fiber profile was evaluated by the expression of myosin heavy chain and SERCA gene by qPCR and myosin protein by using Western blot. The Myod1 and Myog expressions were evaluated by using qPCR. Diaphragm ultrastructure was assessed by electron microscopy, and mitochondrial physiology was investigated by high-resolution respirometry, Western blot, and qPCR. Results Cecal ligation and puncture mice developed moderated sepsis, with a 74% survivor rate at 120 h. The diaphragm mass did not change in CLP mice compared with control, but we observed sarcomeric disorganization and increased muscle thickness (38%) during inspiration and expiration (21%). Septic diaphragm showed a reduction in fiber myosin type I and IIb mRNA expression by 50% but an increase in MyHC I and IIb protein levels compared with the sham mice. Total and healthy mitochondria were reduced by 30% in septic mice, which may be associated with a 50% decrease in Ppargc1a (encoding PGC1a) and Opa1 (mitochondria fusion marker) expressions in the septic diaphragm. The small and non-functional OPA1 isoform also increased 70% in the septic diaphragm. These data suggest an imbalance in mitochondrial function. In fact, we observed downregulation of all respiratory chain complexes mRNA expression, decreased complex III and IV protein levels, and reduced oxygen consumption associated with ADP phosphorylation (36%) in CLP mice. Additionally, the septic diaphragm increased proton leak and downregulated Sod2 by 70%. Conclusion The current model of sepsis induced diaphragm morphological changes, increased mitochondrial damage, and induced functional impairment. Thus, diaphragm damage during sepsis seems to be associated with mitochondrial dysfunction.